Use of learning management system (LMS): a study in a brazilian and portuguese universities - Leone, Roberta de Souza (2022)
Learning Management Systems (LMS) are mainly used as a didactic support for the presential classes. However, because of the tools they provide, they are also essential to support b-learning and e-learning process. Because of this, most universities rely on some LMS through many or all of the courses. This paper describes a study performed in two different universities regarding the students’ perception about the usefulness and the usability of two different LMS: Moodle and Sakai. Through a focus group, students shared their opinion and discussed about their experience. In addition, data from the log of the platforms was also analysed, to assess how teachers use the LMS tools. In general, it can be stated that when the teacher knows how to use the LMS, students feel more comfortable using it and have a better learning experience. Regarding the tools, teachers mostly rely on the repository of documents.